The Drosophila Female Aphrodisiac Pheromone Activates ppk23(+) Sensory Neurons to Elicit Male Courtship Behavior. - Toda, H.; Zhao, X.; Dickson, B.J. (Cell reports, 2012)
Females of many animal species emit chemical signals that attract and arouse males for mating. For example, the major aphrodisiac pheromone of Drosophila melanogaster females, 7,11-heptacosadiene (7,11-HD), is a potent inducer of male-specific courtship and copulatory behaviors. Here, we demonstrate that a set of gustatory sensory neurons on the male foreleg, defined by expression of the ppk23 marker, respond to 7,11-HD. Activity of these neurons is required for males to robustly court females or to court males perfumed with 7,11-HD. Artificial activation of these ppk23(+) neurons stimulates male-male courtship even without 7,11-HD perfuming. These data identify the ppk23(+) sensory neurons as the primary targets for female sex pheromones in Drosophila.